2020
DOI: 10.1021/acs.jchemed.9b00994
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic and Aerobic Respiration in Yeast: Small-Scale Variations on a Classic Laboratory Activity

Abstract: This activity describes a mini- to microscale setup that offers an affordable, reproducible, and accurate method to compare the aerobic and anaerobic respiration of Saccharomyces boulardii, a strain of Saccharomyces cerevisiae. By using cost-effective methodology and standards, students are exposed to concepts such as stoichiometric relationships, yeast metabolism, reaction kinetics, and analytical testing. Yeast CO2 production is measured by reduction of mass (aerobic) and water displacement volumetric change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Saccharomyces spp. strains are facultative anaerobic microbes capable of proliferating under both aerobic and anaerobic conditions [33,34], and it was confirmed that SB and SC could grow in livestock manure under all tested conditions. After 24 h incubation, DNA proportion of SB increased from approximately 20-45% under all culture conditions (SB in aerobic condition, p = 0.0419; SB in anaerobic condition, p = 0.0481).…”
Section: Growth Characteristics Of Yeasts In Manure Depending On Cultmentioning
confidence: 61%
“…Saccharomyces spp. strains are facultative anaerobic microbes capable of proliferating under both aerobic and anaerobic conditions [33,34], and it was confirmed that SB and SC could grow in livestock manure under all tested conditions. After 24 h incubation, DNA proportion of SB increased from approximately 20-45% under all culture conditions (SB in aerobic condition, p = 0.0419; SB in anaerobic condition, p = 0.0481).…”
Section: Growth Characteristics Of Yeasts In Manure Depending On Cultmentioning
confidence: 61%
“…Here we present an undergraduate laboratory experiment that involves labeling of the common baker’s yeast, Saccharomyces cerevisiae , with iron complexes with the goal of introducing cellular biology and coordination chemistry of Fe­(III). This experiment shows the relative ease of handling yeast in comparison to other types of cells as acknowledged in previous articles in this Journal describing beer brewing activities, biochemistry principles, or enzymology of yeast proteins . Coordination chemistry and paramagnetic properties of complexes are also a focus of this laboratory experiment.…”
Section: Introductionmentioning
confidence: 61%
“…This trend continues until approximately 19 h after the initiation of the culture, when a rapid decrease in CO 2 is observed. The exact reason is not clear, but this could be because of the lack of sufficient nutrients and oxygen ( Tervasmäki et al, 2018 ; Koutsokali and Valahas 2020 ). At about the time point of 16 h, dissolved oxygen level reaches zero.…”
Section: Resultsmentioning
confidence: 99%